2019
DOI: 10.1039/c8dt05111a
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal expansion in cubic FeFe(CN)6 Prussian blue analogues

Abstract: A new isotropic negative thermal expansion compound of FeFe(CN)6 has been found, in which the transverse vibrations of N atoms dominate in its NTE behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Consequently, the NTE in Cu 2 P 2 O 7 could result from the coupling twist and rotation of neighbor rigid polyhedra. The NTE nature of Cu 2 P 2 O 7 is entangled with RUMs, which is similar to some framework structure NTE materials, such as ZrW 2 O 8 , ScF 3 , and Prussian blue analogues …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the NTE in Cu 2 P 2 O 7 could result from the coupling twist and rotation of neighbor rigid polyhedra. The NTE nature of Cu 2 P 2 O 7 is entangled with RUMs, which is similar to some framework structure NTE materials, such as ZrW 2 O 8 , ScF 3 , and Prussian blue analogues …”
Section: Resultsmentioning
confidence: 99%
“…and NaZn 13 -type compounds, ferroelectric phase transitions in perovskite (ABO 3 ) group, , size effect in nanoparticles, and valence transition in some oxides. Note that those electron-driven NTE behaviors can present a strong NTE magnitude but a relatively narrow temperature range . As a comparison, the low-frequency phonon driven NTE materials have a merit of wider NTE temperature range but relatively small NTE magnitude, such as oxides, fluorides, , cyanides, , Prussian blue analogues (PBAs), and metal–organic frameworks (MOFs). , All the low-energy phonon driven NTE materials own a common character of framework structure which is in corner shared tetrahedral or octahedral units through M–O–M, M–F–M, or M–CN–M bridges. Generally, flexible framework structures with soft chemical bonds can contribute to a stronger NTE behavior, thus the NTE in oxides or fluorides is generally smaller than that in PBAs or MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…74 Fully oxidized, cubic FeFe(CN) 6 is structurally invariant to hydration. 85 In effect, water acts as a transition modifierit cannot induce phase transitions in cubic PBAs, but it dictates which transition occurs upon hydrostatic compression or Na I inclusion. It is noteworthy that dehydrated Na 2 FeFe(CN) 6 shows the same rhombohedral structure as hydrated MnPt•nH 2 O under compression.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Dehydrated Na 2 FeFe­(CN) 6 crystallizes in R 3̅ (tilt system a – a – a – , ), whereas the hydrated version adopts P 2 1 / n symmetry ( a – a – c + ) . Fully oxidized, cubic FeFe­(CN) 6 is structurally invariant to hydration . In effect, water acts as a transition modifierit cannot induce phase transitions in cubic PBAs, but it dictates which transition occurs upon hydrostatic compression or Na I inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that NTE is induced by the transverse vibrations of the atomic -M-N≡C-M'-linkages through a tension mechanism, since both M-N and M'-C bonds are much softer to bend than to stretch. However, the main vibrational contribution to the NTE comes from the N atoms, since the relative transverse vibrations of the M-N bonds are much larger than that of the M'-C bonds [Figure 17] [113][114][115] . shows the resulting anisotropy of the relative thermal vibrations.…”
Section: Negative Thermal Expansion Materialsmentioning
confidence: 99%